2022
DOI: 10.1111/acv.12765
|View full text |Cite
|
Sign up to set email alerts
|

Exploring multiple dimensions of conservation success: Long‐term wildlife trends, anti‐poaching efforts and revenue sharing in Kibale National Park, Uganda

Abstract: Parks are essential to protect biodiversity and finding ways to improve park effectiveness is a topic of importance. We contributed to this debate by examining spatial and temporal changes in illegal activities in Kibale National Park, Uganda between 2006-2016 and use existing data to evaluate how changes were correlated with the living conditions of people in neighboring communities and patrolling effort. We explore the effectiveness of conservation strategies implemented in Kibale, by quantifying changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…We found that snare occupancy was higher in more remote areas. Other studies have found both inverse (Plumptre et al, 2014; Kimanzi et al, 2015) and positive (Sarkar et al, 2022) relationships between snaring and remoteness. In our landscape, we posit that hunters are spending more time in remote areas with higher wildlife densities.…”
Section: Discussionmentioning
confidence: 93%
“…We found that snare occupancy was higher in more remote areas. Other studies have found both inverse (Plumptre et al, 2014; Kimanzi et al, 2015) and positive (Sarkar et al, 2022) relationships between snaring and remoteness. In our landscape, we posit that hunters are spending more time in remote areas with higher wildlife densities.…”
Section: Discussionmentioning
confidence: 93%
“…The pattern of increase was similar among the sites, and the increase averaged 4.56% across species and areas. Details are presented in (Sarkar et al, 2021). There was a similar increase in the ungulates (see Hou et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in large animal populations can directly affect invertebrate populations through predation or by modifying the forest environment (Chapman et al, 2013; Omeja et al, 2014; Smart et al, 1985). We have assessed changes in the populations of 11 mammal species over 23 years and this information can be found in our previous publications (Chapman, Struhsaker, et al, 2010; Hou et al, 2021; Omeja et al, 2016; Sarkar et al, 2021). We present new detailed information on elephants as their foraging and trampling can significantly modify forest habitats (Coverdale et al, 2016; Smart et al, 1985; Struhsaker et al, 1996; Terborgh et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…To help ensure success, debt should only be offset against demonstrable progress and outcomes, which will take time to measure. We would be amiss if we did not add a cautionary remark that throwing money at a problem without properly assessing what is truly needed and building the capacity to accept the funding will do little to rectify the biodiversity crisis (Sheil, 2001;Sheil et al, 2017;Sarkar et al, 2021).…”
Section: The Cost To Protect Africa's Biodiversitymentioning
confidence: 99%